55 Association between Inflammatory Biomarkers and Severity of Osteoarthritis. (20th December 2019) - Tong, Lynell Roderica Yiu Shyern; Arvindran, Vishnu; Mat, Sumaiyah; Kioh, Sheng Hui; Tan, Maw Pin
Abstract: Introduction: Previous studies have found that older adults with osteoarthritis (OA) were more likely to fall. However, the role of inflammation in OA severity, impaired physical function and increased risk of fall remains unclear. Therefore, the aim of this study is to explore the association between the inflammatory biomarkers and OA severity. Method: This is a cross sectional case-control study which includes 69 individuals aged 55y recruited from orthopaedic clinics, geriatric clinics, primary care and senior citizen groups. Demographic characteristics, medical history, lifestyle factors, Knee Injury and Osteoarthritis Outcome Scores (Koos) were obtained through computer-assisted questionnaires and physical performance were measured. Blood samples were drawn after an overnight fast for a routine laboratory panel. The 20 inflammatory markers were measured and quantified using validated enzyme linked immunosorbent assays included TGFA, IFNG, IL1ra, IL1A, IL1B, IL2, IL3, IL4, IL5, IL6, IL7, IL8, IL9, IL10, IL12P40, IL12P70, IL13, IL15, IL17A and TNFA. Results: Of the 69 participants, mean (SD) age being 66.67 (7.605) and 71% women, 18 (26.1%) reported severe, 13(18.8%) moderate, 20 (29.0%) mild and 18 (26.1%) no OA, women. Significant differences in BMI (p-value<0.01), timed-up and go (p-value=0.01), handgrip strength (p-value<0.05), and all KOOS domain scores (p-value<0.01) were found between the four OA severity groups. Of the 20 inflammatory biomarkers tested, only three biomarkers – TGF-A (p=0.01), IL-6 (p<0.01) and IL-8(p=0.03) were significantly associated with severity of osteoarthritis. Conclusion: More research is needed to see whether this applies to a bigger population and more detailed research needs to be done in regards to TGF-A, IL-6 and IL-8 which shows promise as a severity biomarker for osteoarthritis.